COVID-19 and the cancellation of the 2020 Two Oceans Marathon, Cape Town, South Africa - Swart, K.; Maralack, D. (Sport in Society: Cultures, Commerce, Media, Politics, 2020)
The Two Oceans Marathon, hosted annually in Cape Town, is a premier ultra-marathon in Africa and globally. The 51st edition scheduled for 8-11 April 2020 however three weeks prior it was announced that the event would be cancelled. The decision to cancel was not a popular one and given all the stakeholders involved it was also challenging. Drawing on primary and secondary data, this paper considers factors leading to the decision to cancel, stakeholder engagement and associated orga-nizational and socio-economic impacts. Primary data included key informant interviews with the race director and stakeholders. The findings reveal that the last minute decision to cancel came at a huge cost to the event amidst growing uncertainty, however it is still viewed as the right decision. Regarding lessons learned, race organizers highlighted critical areas including process changes and stakeholder man-agement. A more comprehensive risk management approach is also required.